Preliminary Stage: Student Worksheets Oriented to Higher Order Thinking Skills Based on Learning Styles - Niwanggalih, Puspita; Subchan, Wachju; Wahyuni, Sri (Universitas Pendidikan Ganesha, 2023)
The demands of industry 4.0 are moving towards social society 5.0 to purpose education must be ready. Based on PISA in 2019, Indonesia has low performance quadrant with high equity, means that opportunity to improve critical thinking skills because it has underdeveloped capacity and potential to face the 21st century. Based on the results of survey with teachers and students, researchers found that the unavailability of worksheets base learning styles caused decreasing the student learning interest. This study aims to produce worksheets oriented to higher order thinking skills based on their learning styles. This type of research is development research using the 4D model. The research subjects were 32 even semester VIII grade students and 1 Science teacher at Manbaul Ulum. This research is limited to the analysis stage of school needs towards the development of worksheets oriented to higher order thinking skills based on learning styles using survey techniques. The results of the study show that worksheets that are oriented towards higher order thinking skills based on learning styles need to be developed to train critical thinking skills.